Investigation of the Average Shape and Principal Variations of the Human Talus Bone Using Statistic Shape Model - Liu, Tao; Jomha, Nadr M.; Adeeb, Samer; El-Rich, Marwan; Westover, Lindsey (Frontiers in Bioengineering and Biotechnology, 2020)
Due to the complexity of articular interconnections and tenuous blood supply to the talus, talus fractures are often associated with complications (e.g. avascular necrosis). Currently, surgically fusing the talus to adjacent bones is widely used as treatment to talus fractures, but this procedure can greatly reduce mobility in the ankle and hindfoot. Alternatively, customized talus implants have shown an overall satisfactory patient feedback but with the limitation of high expenses and time-consuming manufacturing process. In order to circumvent these disadvantages, we proposed to design a series of universal talus implants. To this end, this study registered 98 tali (57 males and 41 females) by developing a groupwise registration algorithm. The statistical shape model (SSM) obtained is able to provide valuable insights for the design of universal talus implants. We found that the average male and female talus shapes are geometrically similar, when they were scale to the same volume. Also, our results suggest that in order to obtain an accurate geometry for talus implant design, this first two principal components need to be afforded consideration. Together, these findings provide further understanding into the design of universal talus implants and shed light on the talus statistical shape space.